Miss fortune - Stern, A. J. (Frankly, Frannie, 2012)
Frannie opens a fortune telling business at school after assisting Star, who reads tarot cards at a surprise party for Frannie's father, but soon it becomes clear that making up fortunes can cause a lot of trouble.